Industrial Relations at Queen's: The First Fifty Years - Kelly, Laurence (Relations industrielles / Industrial Relations, 1987)
Relations industrielles/lndustrial Relationscongratulates Queen 's University on its fiftieth anniversary, in 1987, of the founding of the Industrial Relations Centre. A pioneer in the industrial relations field among Canadian universities, Queen's has constantly played a role of leadership. Its historic and continuing efforts are much appreciated by everyone involved in this field of enquiry. In order to further the understanding of the various aspects of the task undertaken, as well as the contribution of the people involved, we are very pleased to present our readers with the following study done by Queen's Industrial Relations Centre.